MODEL KEJAHATAN DUNIA MAYA (CYBERCRIME) SEBAGAI UPAYA PEMBENTUKAN HUKUM NASIONAL - Febriansyah, Ferry Irawan; Indiantoro, Alfalachu; Ikhwan, Afiful (Legal Standing : Jurnal Ilmu Hukum, 2023)
The purpose of this study is to analyze models of cybercrime, namely cybercrime, in order to find out how far the development of forms of crime, whose modus operandi is increasing day by day. The virtual world is part of people's lives so that it cannot be separated from needs. This will later give rise to many new crime models, so that people will be disadvantaged in carrying out activities in cyberspace. This research analysis focuses on empirical legal analysis, namely looking at the social symptoms of people in cyberspace (Internet) in carrying out their daily activities which are vulnerable to crime. The problem that often occurs that is often experienced by the community is education about cyberspace so that they are vulnerable as perpetrators of Cybercrime crimes. This research is very interesting to do along with technological developments, human attitudes and behavior have changed a lot so that new models of crime have emerged in cyberspace.